Study Tide Dynamics and Impact of Coastal Floods on the Settlement Areas of Batam City - Suryani, Rini; Sekarjati, Dhanu (MIYANG, 2023)
Batam City, strategically located as an economic and industrial center in the Riau Islands province, Indonesia, faces challenges stemming from rising sea levels due to climate change and unusual tidal patterns. These factors lead to recurrent coastal flooding and create new issues for coastal areas. This research project has three primary objectives: tidal forecasting, tidal flood hazard mapping, and vulnerability assessment of infrastructure and settlements in Batam City's coastal areas. To achieve these goals, a combination of methods is employed. Tidal forecasts rely on a semimean linear trend approach. Spatial flood analysis considers the Hloss scenario, with the loss distance referring to the peak of the sea flood. Additionally, losses resulting from coastal flooding disasters were assessed using the Economic Commission for Latin America and the Caribbean (ECLAC) budget base planning (RAB) method. The research results reveal that the Batam area experiences two semidiurnal tides with dynamic sea level fluctuations, reaching a peak flood height of 2 meters. Spatial analysis identified several areas affected by tidal flooding, particularly densely populated coastal areas such as Batuaji, Batuampar, Sekupang, and Bengkong subdistricts. These areas, characterized by tidal flats, are particularly vulnerable to significant coastal flooding during high tide. The impact extends to key infrastructure, including roads, mosques, housing, and social facilities, resulting in estimated losses. The number of buildings affected by flood on Batam City is 12,681 units, and the flood affected area covers approximately 10,975.76 hectares, with road infrastructure costs amounting to about US$337,131.36. Field investigations also reveal that several settlements in the region have initiated flood protection measures. However, many settlements are still directly affected, underscoring the immediate need to improve environmental quality in this area.